Mission economy : a moonshot guide to changing capitalism - Mazzucato, Mariana, 1968- (New York : Harper Business, 2021)
"Award-winning author and leading economist Mariana Mazzucato critically examines the current system of capitalism and argues for mission-oriented policies, emphasizing why we need to take big risks to achieve even bigger rewards for our health, society, and environment"--
Keywords: Business and politics; Capitalism; Change management; Economic policy; Organizational change; Sustainable development